2011
DOI: 10.1021/ma102596b
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Dynamics in Miscible Polyisoprene/Poly(p-tert-butylstyrene) Blends

Abstract: Viscoelastic, dielectric, and rheo-optical behavior was examined for miscible blends of high-M cis-polyisoprene (PI) and poly(p-tert-butylstyrene) (PtBS). The slow dielectric relaxation of the blends was exclusively attributed to the global motion of the PI chains having the type-A dipoles. The PI and PtBS chains behaved as the fast and slow (low- and high-friction) components and were well entangled with each other. The dynamics of these chains changed significantly with temperature T. At high T, the blend ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
110
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(121 citation statements)
references
References 61 publications
(187 reference statements)
11
110
0
Order By: Relevance
“…[31][32][33][34] The analysis showed that the PI relaxation was slower in the blends, by a factor of 2-3, than in the iso-t s bulk, possibly because of a topological constraint from the slow PtBS chains. 26 In addition, the entanglement length a in the blends was found to be well described by a simple mixing rule based on the number fraction n of the Kuhn segments of PI and PtBS: 27 a ¼ n PI a This rule, differing from mixing rules assumed in literature, 20,23 is consistent with the current molecular picture that relates the entanglement density to the packing length. [35][36][37] The previous study also examined the global dynamics of the PtBS chains entangled with the PI chains.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…[31][32][33][34] The analysis showed that the PI relaxation was slower in the blends, by a factor of 2-3, than in the iso-t s bulk, possibly because of a topological constraint from the slow PtBS chains. 26 In addition, the entanglement length a in the blends was found to be well described by a simple mixing rule based on the number fraction n of the Kuhn segments of PI and PtBS: 27 a ¼ n PI a This rule, differing from mixing rules assumed in literature, 20,23 is consistent with the current molecular picture that relates the entanglement density to the packing length. [35][36][37] The previous study also examined the global dynamics of the PtBS chains entangled with the PI chains.…”
Section: Introductionsupporting
confidence: 80%
“…[18][19][20][21][22][23] Thus, blends of PI and poly(p-tert-butyl styrene) (PtBS) were chosen as model systems to examine the global dynamics of the components therein. [24][25][26][27] PI has the type-A dipole parallel along the chain backbone and its global motion activates slow dielectric relaxation, 28,29 whereas PtBS has no type-A dipole and is dielectrically inert in long-time scales. 27 This difference between PI and PtBS enabled us to dielectrically examine, without any ambiguity, the global dynamics of PI in the blends.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations